MODIFIKASI ALGORITMA VIGENÈRE CIPHER MENGGUNAKAN METODE CATALAN NUMBER DAN DOUBLE COLUMNAR TRANSPOSITION - Guruh Marindra Pratama; E.Nurmiyati Tamatjita (Compiler, 2015)
Vigenère Cipher is one of the well-known ciphering algorithms of the past. Modifications to Vigenère Cipher algorithm is made to improve its security, making it more difficult to decipher by a cryptanalyst. Due to the nature of the algorithm, these measures have to be taken to maintain the confidentiality of ciphered data.  This research modified the Vigenère Cipher using Catalan Numbers method and Double Columnar Transposition.  Catalan Numbers method is a mathematical method used to randomize the initial key so as to generate a key which is longer and having stronger characteristics; a key which is harder to guess, either by cryptanalysts or by key-deciphering methods. In addition to the first method, Double Columnar Transposition is used to rearrange the position of data in the generated ciphertext in order to make it appear more random, hence slowing down the cryptanalysis process of the encrypted text. Double Columnar Transposition is done by applying columnar transposition twice to the ciphered text. The applied modifications to Vigenère Cipher are then tested using Kasiski Examination. Resulting ciphertexts are known to have randomised characteristics, which made it difficult to guess the ciphering method used to generate the ciphertexts. Tests done using Kasiski Examination {1, 2, 4} proven that the ciphertexts passed the test, hence putting down the possibility of easy deciphering, and the modifications successfully provided a better and stronger encryption to the Vigenère Cipher.